2019
DOI: 10.1186/s12882-019-1578-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patterns and association with mortality and renal outcomes in non-dialysis dependent chronic kidney disease: a matched cohort study

Abstract: BackgroundCancer in patients with chronic kidney disease (CKD) is an added burden to their overall morbidity and mortality. Cancer can be a cause or an effect of CKD. In CKD patients, a better understanding of cancer distribution and associations can aid in the proper planning of renal replacement therapy (RRT) and in the choice of chemotherapeutic agents, many of which are precluded in more advanced CKD. This study aims to investigate the distribution and the association of cancer with mortality, renal progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Accumulating studies have indicated an increased risk of cancer in CKD patients compared with that in non-CKD patients ( Cengiz, 2002 ; Wong et al, 2009 ; Premuzic et al, 2019 ), which might be associated with the decrease in glomerular filtration rate (GFR) or estimated GFR (eGFR) in CKD ( Premuzic et al, 2019 ; Xu et al, 2019 ). And cancer has been recognized as an independent risk factor for all-cause mortality in advanced CKD ( Chinnadurai et al, 2019 ), the risk of which may vary, instead of being linear with the stage of CKD ( Magee, 2014 ; Park et al, 2019 ). End-stage kidney disease (ESKD) is the end stage of CKD, with GFR<15 ml/min/1.73 m 2 ( Kidney Disease: Improving Global Outcomes Glomerular Diseases Work, 2013 ).…”
Section: Potential Mechanisms Of Increased Cancer Incidence Rate In C...mentioning
confidence: 99%
“…Accumulating studies have indicated an increased risk of cancer in CKD patients compared with that in non-CKD patients ( Cengiz, 2002 ; Wong et al, 2009 ; Premuzic et al, 2019 ), which might be associated with the decrease in glomerular filtration rate (GFR) or estimated GFR (eGFR) in CKD ( Premuzic et al, 2019 ; Xu et al, 2019 ). And cancer has been recognized as an independent risk factor for all-cause mortality in advanced CKD ( Chinnadurai et al, 2019 ), the risk of which may vary, instead of being linear with the stage of CKD ( Magee, 2014 ; Park et al, 2019 ). End-stage kidney disease (ESKD) is the end stage of CKD, with GFR<15 ml/min/1.73 m 2 ( Kidney Disease: Improving Global Outcomes Glomerular Diseases Work, 2013 ).…”
Section: Potential Mechanisms Of Increased Cancer Incidence Rate In C...mentioning
confidence: 99%
“…A recent retrospective CKD cohort study 14 using the Salford Kidney Study data showed that cancer was an independent risk factor for all-cause mortality. However, cancer status was not significantly associated with progression to KFRT; this is contrary to our results.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A previous study showed that cancer did not accelerate the rate of kidney disease progression; however, this study was performed with a relatively small cohort of chronic kidney disease (CKD) patients. 14 In the current study, we hypothesized that patients with cancer may have a higher risk of KFRT, and the risk would differ according to cancer types. We used data from the large National Health Insurance Service (NHIS) database to test this hypothesis.…”
Section: Introductionmentioning
confidence: 97%
“…One study showed the higher cancer risk in patients on dialysis for more than 3 years (9 vs 6,5/1000 patient-years) [35]. Despite the higher risk of death due to cancer, cardiovascular diseases are still the main cause of death in this patients group (about 50% vs 4%; 38 vs 7/1000 patient-years) [36][37][38].…”
Section: Survival Of Patients With Cancer On Dialysismentioning
confidence: 99%
“…Another problem in the CKD population, especially in dialysis patients, are unreliable screening tests results. This applies especially for tumor markers, which, in most cases, are macromolecules (3400 kD-5000 kD) ineffectively removed during hemodialysis [36][37][38] except AFP (alpha-fetoprotein) and PSA, whose specificity is high. The role of other antigens in cancer diagnosis is unclear in this patients group (Table 3) [40][41][42][43][44][45].…”
Section: The Diagnostic and Therapeutic Problemsmentioning
confidence: 99%